Morphometrics Observasion and Growth Evaluation of Goats During the Lactation and Post-Weaning Period - Gabriela, Rosemary Angel; Suhardi, Suhardi (JURNAL ILMIAH PETERNAKAN TERPADU, 2025)
This study aims to observe the condition of morphometric variables in kids during the lactation and post-weaning periods, examine the qualitative variables of kids during these periods, and evaluate the growth of kids in both periods. The research was conducted in Lempake, North Samarinda from January to February 2024. The livestock used consisted of 40 local kids, such as Kacang and Jawarandu goats, with 20 kids in the lactation period and 20 in the post-weaning period, all under 1 year old, approximately 4-8 months. Descriptive analysis was conducted qualitatively, and quantitative data were analyzed using the t-test method with Statistical Package for the Social Sciences (SPSS) 26 software. The morphometric variables indicated that kids showed significant differences in quantitative data during the post-weaning period compared to the lactation period. Qualitative variables showed that the dominant skin color was reddish and white, the predominant hair color was black and white, or white, brown, and black, and there was a change in horn shape towards a more perfected form after weaning. Daily weight gain performance showed an increase in post-weaning kids compared to the lactation period, indicating that kids experienced better growth after the weaning process.